К истории открытия дидрахмы боспорского царя Спартока [Igor P. Medvedev. On the Discovery of Spartocus’ Didrachm] - Медведев, И. П. (Hyperboreus, 2011)
The author publishes extracts from the correspondence between Nikolaj P. Rum’ancev, a famous Russian antiquarian and coin collector, and his friend and adviser academician Philipp I. Krug concerning the discovery of king Spartocus’ didrachm, which was later published by Heinrich Koehler.